2021
DOI: 10.9767/bcrec.17.1.12347.103-112
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous N-doped TiO2 by Using Peroxo Sol-Gel Method for Photocatalytic Reduction of Cd(II)

Abstract: Porous N-doped TiO2 photocatalyst was successfully synthesized by an environmentally friendly peroxo sol-gel method using polyethylene glycol (PEG) as a templating agent. Here, the effect of PEG addition to the aqueous peroxotitanium solutions on the structure, pore properties and photocatalytic activity of the obtained photocatalysts was systematically studied. The prepared photocatalysts were characterized by X-ray diffraction (XRD), UV-Vis diffuse reflectance spectroscopy (DRS), and Brunauer-Emmett-Teller (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…This is different when compared to pure TiO2, which is pure white. This color change was caused by modifying the TiO2 band gap by nitrogen doping, which shifts the optical absorption of this photocatalyst [22]. A detailed explanation of this information will be discussed in the optical properties section supported by UV-Vis spectroscopy analysis.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…This is different when compared to pure TiO2, which is pure white. This color change was caused by modifying the TiO2 band gap by nitrogen doping, which shifts the optical absorption of this photocatalyst [22]. A detailed explanation of this information will be discussed in the optical properties section supported by UV-Vis spectroscopy analysis.…”
Section: Resultsmentioning
confidence: 94%
“…It is confirmed that since the undoped TiO2 has a strong absorption on the UV light, it appears in pure white color. In contrast, shifting absorption to the visible region caused all the synthesized N-doped TiO2 to appear yellowish [22]. Figure 3 shows the relationship between the absorption coefficient and the absorbed energy/photon (hv).…”
Section: The Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 ] The optical absorbance of TiO 2 in UV and Vis regions limits the generated bandgap (>3.2) that properties decrease the generated electrons in the conducting level and so decreasing its efficiency for gas sensing based on the electric charge attraction. [ 13 ] He et al [ 14 ] used Na 0.23 TiO 2 /TiO 2 and TiO 2 for NOx materials, in which the sensitivity increased very much after doping the TiO 2 with Na atoms.…”
Section: Introductionmentioning
confidence: 99%